Paranormal belief and well-being: The moderating roles of transliminality and psychopathology-related facets - Dagnall, Neil; Denovan, Andrew; Drinkwater, Kenneth Graham; Escolà-Gascón, Álex (Frontiers in Psychology, 2022)
Evaluation of prior research suggests that belief in the paranormal is more likely to be associated with negative psychological functioning, when presented alongside cognitive-perceptual factors that askew thinking and insight. The current study examined this notion using a sample of 3084 participants (1382 males, 1693 females, 9 non-binary). Respondents completed self-report measures assessing Paranormal Belief, Transliminality, psychopathology-related characteristics (Schizotypy and Manic-Depressive Experience), and well-being (Perceived Stress and Somatic Complaints). Responses were analysed via correlations and moderation. Paranormal Belief correlated positively with Transliminality, psychopathology-related measures, Perceived Stress, and Somatic Complaints. Moderation analyses revealed that Transliminality and psychopathology-related variables (i.e., the Unusual Experiences and Cognitive Disorganisation subscales of schizotypy, and Manic-Depressive Experience) interacted with Paranormal Belief in complex ways and were allied to higher scores on negative well-being outcomes. This indicated that within paranormal believers, Transliminality and specific psychopathology-related variables in combination predicted susceptibility to negative well-being outcomes.